Security issues in distributed data storage & its solutions - Punitha, A. Amali Angel; Indumathi, G. (ICCPEIC : 2017 International Conference on Computation of Power, Energy Information and Commuincation : 22-23 March 2017, 2017)
Privacy is mandatory to prevent unapproved clients from contact with the sensitive data as it is subject to illicit disclose and access once it outsourced. Genuineness can keep outsourced data from being returned and altered. The Distributed reckoning is the latest innovation which gives distinctive robust free administrations through the web. The virtual cloud server permits the client to store their information on the cloud without stressing over accuracy & integrity of the data. The distributed data storage has numerous benefits over local data storage. The user can upload data to the cloud and get those data at anytime and anywhere with no extra burden. The User doesn't need to stress over storage and maintenance of cloud data. In any case, as the data are put in the remote place how users will get the affirmation about stored information. Subsequently, distributed storage ought to have some system which will determine storage correctness and trustworthiness of data stored on a cloud. The main issue of distributed storage is security. Numerous scientists have proposed their work or new encryption algorithms to accomplish security or to resolve this security issue. The proposed encryption scheme leverages to build a secure data storage to significantly improve the security.